Functional role of 18 LysR-Type transcriptional regulators of Salmonella enterica serovar Typhi - Victor M. Hernández; Yitzel Gama-Martínez; Lorenzo Segovia; Ismael Hernández-Lucas (PLoS ONE, 2025)
Salmonella enterica serovar Typhi ( S. Typhi) is the etiological agent of typhoid fever in humans. The genomic organization of this bacterium shows the presence of 41 LysR-Type transcriptional regulators (LTTRs). Remarkably, 23 of these LTTRs have orthologous proteins in different bacterial species where they have been characterized. However, the remaining 18 LTTRs are annotated as hypothetical proteins and their role is not described yet. In this work we report the role of these 18 proteins. We show that these transcriptional factors contain the two domains characteristic of the LTTR family. Furthermore, these LTTRs are involved in the resistance to bile salts, antimicrobial peptides, high temperature, motility, biofilm formation and porin regulation. Thus, LTTRs are essential in the S . Typhi response to stresses in the human hosts and in different biological process necessary for efficient infection.